PENGARUH PENGGORENGAN DAN CARA PENGERINGAN TERHADAP SIFAT ROTAN BALUKBUK (CALAMUS BURCKIANUS) DAN ROTAN SEUTI (CALAMUS ORNATUS) - Efrida Basri; Suparman Karnasudirdja (Jurnal Penelitian Hasil Hutan, 1987)
This paper presents the result of laboratory drying tests on 1wo rattan species. The samples from each species were devided into two groups. The first group was fried in kerosene before  drying,  and the second was left unfried.   Each group  was then subjected  to two drying conditions, namely drying  under roof  (in-door)  and  out-door. The  test were  terminated  when  the samples  reached equilibrium  moisture content, i.e . approximately 16%.  The result of evaluation  rattan qualitv  based on colour  is presented  together  with their drying speed. It shows that  both balukbuk  and seuti rattans when fried in kerosene dry faster than  when untried. However,   frying seems to  produce  darker colour after drving.